The Legal Implications of a Food Service Provider’s Breach of Obligations a Comparative Study - Hussein, Birk Faris; Mahmoud, Imad Abdullah (Journal of Ecohumanism, 2024)
When a food service provider breaches their obligations towards the recipient of the food service, and the elements of contractual liability are established, this gives the recipient the right to seek redress for all damages arising from such a breach. Contractual liability of the food service provider generally arises when they fail to fulfill their obligations as stipulated by law or agreement. The resulting legal effect of this breach, naturally, is compensation.